Privacy in Employment Relationship - Senčur Peček, Darja (Anali PAZU, 2022)
The paper is dealing with selected questions of protection of employee’s privacy in Republic of Slovenia. In regulation of this question proper balance between employer’s right to control employees and employee’s right of privacy on working place has to be found. Slovene legislation is regulating the protection of employee’s personal data and video-surveillance on the working place, but this can’t be said for some other views of protection of employee’s privacy. The answer on the question where are the borders for employer’s interference into the employee’s privacy (e.g. the supervision of usage of communication means by employee) will have to be found by court practice.
Keywords: privacy; protection of privacy; employee; employment relationship